The use of magnetic resonance imaging using compression sensor measurement in the diagnosis of spondylitis due to brucellosis and the study of distinguishing spinal tuberculosis. (15th July 2020) - Yang, Jinyong; Tang, Yanyan; Wu, Wenli; Pathan, Sakib-Khan
Highlights: MRI can improve the diagnosis efficiency of brucellosis. Some Brucella spine infected is located in the lumbar spine, with less edge damage. The spinal tuberculosis and brucellosis spondylitis can be distinguished by MRI. Abstract: Under the guidance of the theory of pressure sensor measurement, magnetic resonance imaging (MRI) was used to improve the efficiency of the examination. The clinical MRI data of 30 patients with Brucella spondylitis and 30 patients with spinal tuberculosis in the Infectious Disease Hospital are analyzed retrospectively. The similarities and differences of clinical manifestations between the two diseases Brucella spondylitis and spinal tuberculosis are obtained. From the comparison of the distribution of lesions, the number and number of cases of lumbar spine injury in two groups are far more than that of other lesions. Abnormal low signal of T1w1 and high signal of T2w1 can be found in pathological paravertebral soft tissue of patients with Brucella spondylitis. In addition, the spine infected by Brucella is usually located in the lumbar spine, with less damage and less edge damage. However, the destruction of vertebral body is very serious, kyphosis and multisegmental paravertebral abscess are obvious, and the risk of tuberculosis infection will also affect adjacent organs. According to the difference of imaging results, the typical spinal tuberculosis and brucellosis spondylitis can be distinguished, which was of great value and significance for diagnosis and differentiation.